USING COLLABORATIVE LEARNING APPROACH TO IMPROVE LEARNER’S MENTAL LEXICON OF WORD ASSOCIATION: Received: 27th August 2021; Revised: 07th December 2021, 31st January 2022, 03rd February 2022; Accepted: 04th February 2022 - Susantiningdyah, Healty; Inayati, Nina; Dirgantari, Alfi Suci; AS, Hilga Clararissa (PUPIL: International Journal of Teaching, Education and Learning, 2022)
A collaborative learning approach has been identified to lessen anxiety and allow more comprehensible inputs to be processed cognitively to result in meaningful outputs. This study specifically examines the effectiveness of the collaborative learning approach and its best fit model supplemented with several techniques to improve students’ mastery of the mental lexicon of the word association. This Classroom Action Research involved 60 college students in their senior years in Institut Teknologi Kalimantan. The data collection involved two cycles in which each cycle employed planning, implementation, analysing learning activities and learning outcome and finally reflection. To gain insight through each cycle, a cloze test and a survey were administered. Furthermore, the result was analysed qualitatively and the finding reveals a significant improvement in terms of the mental lexicon of word association repertoire especially in cycle 2. The percentage of the students meeting the criteria of success doubled at 71.67% while the students’ learning perception throughout each cycle was successfully maintained. Collaborative learning also helped most students to create a positive perception to level up their mental lexicon mastery.